Mga elemento ng panlipunang pananaw ng simbahan - Balajadia, Basilio P. (Manila : De La Salle University Press, 2002)
Perceptions of Filipinos on the socio-economic role of Catholic church in their lives.
Includes bibliographical references (p. 165-167) and index.
College Students
In Tagalog.
Keywords: Church and social problems -- Philippines -- Catholic Church; Philippines -- Social conditions -- 1986-; Philippines -- Economic conditions -- 1946-